Feasibility and development of a cariogenic diet scale for epidemiological research. Issue 3 (20th February 2019) - Amezdroz, Emily; Carpenter, Lauren; Johnson, Shae; Flood, Victoria; Dashper, Stuart G.; Calache, Hanny; Gussy, Mark; Waters, Elizabeth
Abstract : Background: Diet cariogenicity plays a major role as both a protective and risk factor in the development of early childhood caries (ECC). Aim: Develop a scale measuring the cariogenicity of foods and beverages and employ it to describe the cariogenicity of young children's diets and predict dental caries outcomes. Design: Scores of cariogenicity and consumption frequency were applied to food frequency questionnaire (FFQ) collected from an Australian children's cohort study with three time‐points of data. One‐way ANOVA, with post hoc Tukey test compared mean cariogenic scale measured at 18 months between the subsample of children with caries classification at age 5 years. Results: At 6 months, children's mean cariogenic score was 10.05, increasing to 34.18 at 12 and 50.00 at 18 months. Mean cariogenic scale score at 18 months was significantly higher in children with advanced disease at 5 years (mean scale score: 59.0 ± 15.9) compared to those that were healthy (mean score 47.7 ± 17.5, P  = 0.007) or had mild‐moderate disease (mean score 48.2 ± 17.3, P  = 0.008). Conclusions: The cariogenic diet scale provides a useful indication of the increasing cariogenicity of children's diets with age and highlights the incorporation of discretionary choice foods and beverages into the diets of young children much earlier than nutritionally recommended.